The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1007/978-3-319-39441-1_8
|View full text |Cite
|
Sign up to set email alerts
|

Topological Descriptors for 3D Surface Analysis

Abstract: Abstract. We investigate topological descriptors for 3D surface analysis, i.e. the classification of surfaces according to their geometric fine structure. On a dataset of high-resolution 3D surface reconstructions we compute persistence diagrams for a 2D cubical filtration. In the next step we investigate different topological descriptors and measure their ability to discriminate structurally different 3D surface patches. We evaluate their sensitivity to different parameters and compare the performance of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 26 publications
1
11
0
Order By: Relevance
“…Moreover, we verify the validity of our results on an extended large-scale dataset [11]. To provide the complete picture of our analysis we include the results from [9] in this paper.…”
Section: Introductionsupporting
confidence: 63%
See 2 more Smart Citations
“…Moreover, we verify the validity of our results on an extended large-scale dataset [11]. To provide the complete picture of our analysis we include the results from [9] in this paper.…”
Section: Introductionsupporting
confidence: 63%
“…For both descriptors we select those parameters for which they have yielded best results in our previous investigation [9]. See Tab.…”
Section: Topological Baseline Descriptorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Kramár et al (2016) use sublevel set persistence to summarize the complicated spatiotemporal patterns that arise from dynamical systems modeling fluid flow, including turbulence (Kolmogorov flow) and heat convection (Rayleigh-Bénard convection). With sublevel set persistence, Zeppelzauer et al (2016) improve 3D surface classification, including on an archaeology task of segmenting engraved regions of rock from the surrounding natural rock surface. In a task of tracking automobiles, Bendich et al (2016a) use the sublevel set persistent homology of driver speeds in order to characterize driver behaviors and prune out improbable paths from their multiple hypothesis tracking framework.…”
Section: Examples Measuring Local Geometrymentioning
confidence: 99%
“…They showed that estimated standard deviations of the errors indicate the robustness and classification results. Zeppelzauer et al [24] investigated different topological descriptors and measured their ability to discriminate structurally different 3D surface patches. The study revealed that topological descriptors are (i) robust, (ii) yield state-of-the-art performance for the task of 3D surface analysis, and (iii) improve classification performance when combined with non-topological descriptors.…”
Section: Introductionmentioning
confidence: 99%